Evaluation of clinical outcomes after COMBO stent treatment in patients presenting with acute coronary syndrome. Issue 2 (1st February 2017) - Kalkman, Deborah N.; Woudstra, Pier; Lu, Huangling; Menown, Ian B.A.; den Heijer, Peter; Suryapranata, Harry; Iñiguez, Andrés; Arkenbout, Karin E.; van't Hof, Arnoud W.J.; Muller, Philippe; Erglis, Andrejs; Tijssen, Jan G.; et al.
Abstract : Background: Patients presenting with acute coronary syndrome (ACS) are at increased risk of complications after percutaneous coronary intervention with stent placement compared to patients with stable angina (SA) treated in an elective setting. The novel pro‐healing COMBO stent is a bio‐engineered drug eluting stent designed to promote vessel healing. Therefore, the stent may reduce this difference in clinical outcomes between elective and ACS‐patients and prevent late stent thrombosis. Methods and Results: The European, prospective, multicenter, 1000 all‐comers patient REMEDEE registry evaluates clinical outcomes after COMBO stent placement in ACS‐ and elective patients. The primary endpoint at 12 months is target lesion failure (TLF), a composite of cardiac death, target‐vessel myocardial infarction and target lesion revascularization. A total of 49.9% (n = 498) of patients presented with acute coronary syndrome. TLF was 7.1% in ACS patients, definite and probable stent thrombosis was observed in 0.5% of ACS patients and in all within 9 days post stenting. We found no significant difference in TLF between ACS and non‐ACS patients and a low overall rate of TLF. Conclusions: The COMBO stent is a safe and efficient device for patients presenting with ACS. Low ST rate and only early stent thrombosis were observed. © 2017 Wiley Periodicals, Inc.